2020
DOI: 10.1186/s13018-020-01764-w
|View full text |Cite
|
Sign up to set email alerts
|

Design a novel integrated screw for minimally invasive atlantoaxial anterior transarticular screw fixation: a finite element analysis

Abstract: Purpose: To design a new type of screw for minimally invasive atlantoaxial anterior transarticular screw (AATS) fixation with a diameter that is significantly thicker than that of traditional screws, threaded structures at both ends, and a porous metal structure in the middle. The use of a porous metal structure can effectively promote bone fusion and compensate for the disadvantages of traditional AATSs in terms of insufficient fixation strength and difficulty of bone fusion. The biomechanical stability of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…2 ). The cortical bone, facet joint surface and cartilage endplate were meshed by shell elements, with thickness of 1.5 mm, 0.2 mm and 0.4 mm [ 14 ], respectively. The intervertebral disc was divided into the nucleus pulposus and the annulus fibrosus, with the nucleus pulposus accounting for 1/3 of the intervertebral volume [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…2 ). The cortical bone, facet joint surface and cartilage endplate were meshed by shell elements, with thickness of 1.5 mm, 0.2 mm and 0.4 mm [ 14 ], respectively. The intervertebral disc was divided into the nucleus pulposus and the annulus fibrosus, with the nucleus pulposus accounting for 1/3 of the intervertebral volume [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Currently, studies have demonstrated that posterior surgery represented by C1 lateral mass-C2 pedicle screw fixation achieves reliable stability and has high fusion rates and excellent clinical outcomes, so it has become the commonly used method for atlantoaxial fixation [ 6 8 ]. However, the posterior approach may present unsatisfactory decompression and reduction results in some cases in addition to the risk of vertebral artery injury and causing more extensive soft tissue damage than the anterior approach [ 9 , 10 ]. In particular, the anterior approach is suitable for patients with a vertebral artery with an abnormal course and patients with no posterior bony structure [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…They discovered that the bone tissue could not just bind at the interface of the implant but also grow through the lateral holes into the interior of the implant, where it tightly bound with the internal sidewalls of the implant, achieving secondary reinforcement and promoting bone fusion. Zhang et al 21 designed a novel atlantoaxial anterior transarticular screw with enlarged thread structures at both ends and a porous cylinder in the middle. The finite element analysis confirmed that the novel screw could provide improved biomechanical stability.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al . 21 designed a novel atlantoaxial anterior transarticular screw with enlarged thread structures at both ends and a porous cylinder in the middle. The finite element analysis confirmed that the novel screw could provide improved biomechanical stability.…”
Section: Introductionmentioning
confidence: 99%